Increased usage of doxycycline for young children with Lyme disease - Thompson, Amy D.; Neville, Desiree N.; Chapman, Laura L.; Balamuth, Fran; Ladell, Meagan M.; Kharbanda, Anupam B.; Aresco, Rachael; Nigrovic, Lise E. (Frontiers in Antibiotics, 2024)
Background: The 2018 Infecous Disease Commitee of the American Academy of Pediatrics stated that up to three weeks or less of doxycycline is safe in children of all ages. Our goal was to examine trends in doxycycline treatment for children with Lyme disease. Methods: We assembled a prospecve cohort of children aged 1 to 21 years with Lyme disease who presented to one of 8 parcipang Pedi Lyme Net centers between 2015 and 2023. We defined a Lyme disease case with an erythema migrans (EM) lesion or posive two-er Lyme disease serology categorized by stage: early-localized (single EM lesion), early-disseminated (mulple EM lesions, cranial neuropathy, meningis, cardis), and late (arthris). We compared doxycycline treatment by age and disease stage and used logisc regression to examine treatment trends. Results: Of the 1,154 children with Lyme disease, 94 (8.1%) had early-localized, 449 (38.9%) earlydisseminated, and 6,114 (52.9%) late disease. Doxycycline treatment was more common for older children (83.3% > 8 years vs. 47.1% < 8 years; p < 0.001) and with early-disseminated disease (77.2% early-disseminated vs. 52.1% early-localized or 62.1% late; p < 0.001). For children under 8 years, doxycycline use increased over the study period (6.9% 2015 to 67.9% 2023; odds rao by year 1.45, 95% confidence interval 1.34, 1.58). Conclusions: Young children with Lyme disease are frequently treated with doxycycline. Prospective studies are needed to confirm the safety and efficacy of doxycycline in children younger than 8 years, especially for those receiving longer courses of therapy.